A value chain analysis of the formal and the informal economy: a case study of South African Breweries and shebeens in Soweto - Tsoeu, Mariane (My University, 2009)
Abstract South African Breweries Limited (SAB) is the dominant player in the beer market within the South African economy. The company owns 95 per cent of the market. This astounding dominance in the market is strongly linked to the informal economy. Over 82 per cent of SAB beers are consumed in illegal shebeens in townships like Soweto. During the height of apartheid, SAB went against the apartheid government and formed illegal relationships with township shebeens in order to increase their market in these areas. Thus, SAB was instrumental in the expansion of the informal retailing of beer in shebeens. SAB also grew from this informality. The very backbone of SAB is the township market, which is called the quarts (the 750 ml bottled beer) market. Even at present SAB uses shebeens to increase its market share. Given this, there is a clear relationship between the formal and the informal economies. The main reason that SAB initiated relations with shebeens was because these enterprises formed the most crucial part of their value chain. The value chain analyses demonstrate the linkages between the formal and the informal economies through a case study of SAB and shebeens in Soweto.